The selfies and the “tombamento” body: reflections from a sound self-portrait - Edmea Oliveira dos Santos; Carina D'Ávila (Perspectiva, 2019)
This article is part of a research-training that took place at the Spectaculu School of Art and Technology in 2016, with 29 students of Photography and Image Treatment in the discipline "Olhar" (View), whose objective is to enhance their aesthetic experiences. The research-training methodology (MACEDO, 2000; JOSSO, 2004; SANTOS, 2002) performs in a creative way in which it seeks to look at the educational experience to produce new knowledge and approaches. And in this meeting, the term “Tombamento” became increasingly evident from a device used in the classroom called "Autorretrato Musical" (Musical Self Portrait) that is a self-image connected to a song. Basically, the process of this device is divided into three: self-design and writing of their training networks; talk about yourself and listen to the other; creation and production of sound self-image. The objective of this article, therefore, is to examine this experience by exchanging the notions of “Tombamento” with effects of presence and meaning debated by the contemporary author Gumbrecht (2010). It is concluded that Tombamento is an ethical-aesthetic manifesto in itself, that is, in the very body of a contemporary generation composed of an " confrontational" youth who has formed in the periphery and the internet and who creates new narratives and references to theirs, gaining new spaces of action, being appropriated in mass media and subject to much criticism.